2004
DOI: 10.1002/bdrb.20004
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac abnormalities induced by zinc deficiency are associated with alterations in the expression of genes regulated by the zinc‐finger transcription factor GATA‐4

Abstract: Zinc (Zn) deficiency during pregnancy results in a wide variety of developmental abnormalities. The objective of this study was to determine if expression of cardiac developmental genes regulated by Zn-finger transcription factors could be modulated during dietary Zn deficiency. Rats were fed 0.5 (low Zn) or 90 (controls) microg Zn/g diet throughout pregnancy. Fetal development was examined and RNA isolated at gestation day (GD) 13 and 20. Cardiac abnormalities were detected at GD 20 in 82% of fetuses from dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 39 publications
3
24
0
1
Order By: Relevance
“…Our study also suggests that Zn deficiency (regardless of its cause) may be involved in the pathogenesis of LVNC. This is in agreement with previous studies showing that maternal Zn deficiency resulted in multiple forms of cardiac abnormalities including thin ventricular wall and irregular trabeculae (21,22). Genetic testing for SLC39A8 mutations in cases of LVNC may be worth consideration.…”
Section: Slc39a8supporting
confidence: 92%
See 1 more Smart Citation
“…Our study also suggests that Zn deficiency (regardless of its cause) may be involved in the pathogenesis of LVNC. This is in agreement with previous studies showing that maternal Zn deficiency resulted in multiple forms of cardiac abnormalities including thin ventricular wall and irregular trabeculae (21,22). Genetic testing for SLC39A8 mutations in cases of LVNC may be worth consideration.…”
Section: Slc39a8supporting
confidence: 92%
“…Zn deficiency has been shown to result in developmental defects including multiple types of cardiac abnormalities (21,22). Zn homeostasis is primarily reguIsolated left ventricular noncompaction (LVNC) results from excessive trabeculation and impaired myocardial compaction during heart development.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that zinc deficiency leads to oxidation of cysteines in zinc-finger transcription factors, which would result in loss of activity. In a key publication in Birth Defects Research Part B, Duffy et al (2004) showed that in fetal hearts, zinc deficiency alters the DNA-binding activity of GATA-4, a zinc-finger transcription factor that subsequently led to a down-regulation of downstream gene expression, e.g., alpha-myosin heavy chain and cardiac troponin-I, that are critical for early cardiac development . Similar zinc deficiency-induced reductions in gene expression in extraembryonic tissues have been noted in the MT-1 gene that is regulated by the zinc-finger-containing transcription factor, MTF-1 (Andrews et al, 2001).…”
Section: Cell-signaling Cascadesmentioning
confidence: 99%
“…Heart development can be particularly sensitive to Zn deficiency. In rats, severe maternal Zn deficiency has been associated with a high incidence of fetal heart anomalies, which were speculated to result in part from a reduced expression of heart-specific genes that contain Zn-finger transcription factor binding sites in their promoter sequence [9]. Although the pathophysiological mechanisms that underlie the heart defects noted above have yet to be delineated, it is recognized that the effects of Zn deficiency are multifaceted.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the majority of heart anomalies observed in Zn-deficient rat fetuses seem to involve the development of the innominate artery, the great vessels, and the outflow tract [9], we speculated that the heart defects observed with developmental Zn deficiency are due in part to an insult on the population and distribution of NCC as a result of increased cell death. To test this hypothesis, we assessed heart histology at different time points to determine if the abnormal morphology observed in response to Zn deficiency correlated with changes in the distribution of apoptotic cells in fetal rat hearts.…”
Section: Introductionmentioning
confidence: 99%